The Impact of Tennis Rules on Playing Styles and Player Tactics - Muhanned Nazar Kzar; Dhay Salim Hamza (Eximia, 2025)
This research examines the impact of tennis rules on players' playing styles and tactics. Tennis is one of the most popular sports in the world, characterized by unique competitive elements including precision, speed, and strength. Playing styles and tactical approaches are influenced by players' understanding of the game's rules and the strategic tactics permitted within those rules. By analyzing how different regulations, such as the point system, serving rules, and gameplay alterations affect player performance, this research aims to demonstrate how playing styles have evolved to become more tactical and intelligent. The issue will be studied by analyzing how players respond to different game rules and whether these rules push them to develop skills and alter their styles or not. The research aims to identify the most common playing styles based on these rules while considering their overall impact on player performance. The study will present hypotheses related to how specific aspects of game rules affect tactical approaches, and it will address various fields the research touches upon, such as the psychological, physical, and social aspects of tennis. The findings of this research will represent a significant contribution to the literature related to tennis and skill development in this sport.